Collaboration between traditional healers and psychiatrists in Sudan - Sorketti, E. A. (Int Psychiatry, 2010)
The importance of traditional healing in low- and middle-income countries cannot be underestimated. It is generally perceived as part of the prevailing belief system and traditional healers are often seen as the primary agents for psychosocial problems in these countries; estimates of their service share range from 45% to 60% (World Health Organization, 1992). The World Health Organization (2000) estimated that 80% of people living in rural areas in low- and middle-income countries depend on traditional medicine for their health needs.